A multi-tissue de novo transcriptome assembly and relative gene expression of the vulnerable freshwater salmonid Thymallus ligericus - Giulia Secci-Petretto; Steven Weiss; André Gomes-dos-Santos; Henri Persat; André M. Machado; Inês Vasconcelos; L. Filipe C. Castro; Elsa Froufe (Genetica, 2024)
Freshwater ecosystems are among the most endangered ecosystems worldwide. While numerous taxa are on the verge of extinction as a result of global changes and direct or indirect anthropogenic activity, genomic and transcriptomic resources represent a key tool for comprehending species' adaptability and serve as the foundation for conservation initiatives. The Loire grayling, Thymallus ligericus , is a freshwater European salmonid endemic to the upper Loire River basin. The species is comprised of fragmented populations that are dispersed over a small area and it has been identified as a vulnerable species. Here, we provide a multi-tissue de novo transcriptome assembly of T. ligericus . The completeness and integrity of the transcriptome were assessed before and after redundancy removal with lineage-specific libraries from Eukaryota, Metazoa, Vertebrata, and Actinopterygii. Relative gene expression was assessed for each of the analyzed tissues, using the de novo assembled transcriptome and a genome-based analysis using the available T. thymallus genome as a reference. The final assembly, with a contig N50 of 1221 and Benchmarking Universal Single-Copy Orthologs (BUSCO) scores above 94%, is made accessible along with structural and functional annotations and relative gene expression of the five tissues (NCBI SRA and FigShare databases). This is the first transcriptomic resource for this species, which provides a foundation for future research on this and other salmonid species that are increasingly exposed to environmental stressors.